Development of an Android-friendly E-video to raise awareness of E-waste management as part of the Swachch Bharat Mission in Pali District, Rajasthan - Sinha, Latika Nath; Sharma, Kumkum; Choudhary, Yachana; Purohit , Laxmikant; Dube, Salil; Choudhary, Sanjay (Indian Journal of Community Health, 2025)
Background: Electronic/Electrical products, which are of no use anymore, are referred to as electronic waste. Electronic waste causes contamination of the environment with heavy metals during the process of informal dismantling. Initiatives such as Extended Producer Responsibility and Design for Environment, together with the 3Rs (Reduce, Reuse, and Recycle), were suggested by the Swachch Bharat Mission (SBM2.0). The purpose of this study was to evaluate urban dwellers' knowledge and practices around e-waste and raise awareness through an e-video created by Phase III MBBS students. Objectives: 1. To estimate the knowledge, attitudes, and practices on E-waste management in PALI urban. 2. To increase awareness and assess satisfaction levels among the residents regarding prepared E video. Methods: 384 residents of the UHTC's catchment region participated in an analytical cross-sectional study using the purposive sampling technique. They were interviewed using a semi-structured pre-validated questionnaire on e-waste-related knowledge and practice parameters and were shown a video on recommended disposal practices. Data was analyzed using Epi info 7.2 using appropriate tests of significance. Results: Among respondents, 95% had heard of E-waste from media. Domestic e-waste generated was kept at home (3.5%), given to the kabari wala/scrap collector (73%), exchanged at electronic shops (4.2%), or thrown in dustbins (3.5%). Some knew of companies willing to collect their e-waste (16%) but only 6% utilized that service and 4 % knew what was finally done with it. Younger ages <27 years and Higher levels of education were found to be statistically significant with respect to better knowledge and practices (p-value <0.05). The e-video increased knowledge of respondents by 68% and 83% were satisfied by its content. Conclusions: No streamlined system of disposal, collection, or dismantling of e-waste existed in the town and the video on recommended practices was well received. Increased awareness of E-Waste Tax Credits for Manufacturers, E-waste ATMs for encouraging recycling, and E-waste tracking and certification are feasible solutions.